Composition for smelting scale inhibition alloy, filter material, smelting membrane and preparation method thereof
By reducing the nickel content and increasing the iron content in the composition for scale-resisting alloy smelting, combined with the belt smelting process, a scale-resisting alloy filter with low cost, strong corrosion resistance and excellent scale-resisting performance is prepared, and the cost and corrosion resistance problems caused by high nickel content in the prior art are solved.
Patent Information
- Application Number
- CN202411601557.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing scale-resistance alloy filters have high nickel content, resulting in high cost and poor corrosion resistance.
A composition for smelting of scale-resistant alloys is provided, with a low nickel content and a high iron content. The scale-resistant alloy filter material is prepared by a belt-shafting process to improve grain refinement and corrosion resistance.
The cost of scale-resistance alloy filter is reduced, its corrosion resistance and scale-resistance properties are improved, and the recovery rate is improved.
Smart Images

Figure CN119663046A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of anti-scaling alloys and smelting thereof, and in particular to a composition for smelting anti-scaling alloys, a filter material, a smelting membrane and a preparation method thereof. Background Art
[0002] Anti-scaling alloy filter media is a kind of anti-scaling material with a service life of 3 to 5 years. Different metals in the anti-scaling alloy have different electrode potentials. The combination of different metals can form an activation current in the water flow. The activation current can change the movement and distribution of calcium and magnesium ions in the water, and then inhibit the scaling of calcium and magnesium ions in the water, achieving the effect of anti-scaling.
[0003] In the relevant technology, the quaternary alloy of copper, nickel, zinc and tin is generally used as the main material, and other trace elements are used as the auxiliary materials. The ingots are formed by atmospheric smelting and casting, and then the ingots are turned to form anti-scaling alloy turning materials, which are then screened and cleaned to form anti-scaling alloy filter materials.
[0004] In order to cope with the problem of poor corrosion resistance of the anti-scaling alloy filter material due to the large difference in alloy structure caused by inconsistent cooling rates between the core and the surface during atmospheric smelting and casting, the anti-scaling alloy filter material contains more nickel, which usually needs to be added to a mass proportion of more than 10%, resulting in a higher cost of the anti-scaling alloy filter material. Summary of the invention
[0005] Based on this, some embodiments of the present application provide a composition for smelting a scale-inhibiting alloy, in which the nickel content is low and the iron content is relatively high, thereby reducing costs. When the scale-inhibiting alloy smelting composition is smelted by belt smelting, the scale-inhibiting alloy has a high degree of grain refinement and no obvious segregation, and has excellent corrosion resistance and scale inhibition performance, and can improve the recovery rate, further reducing costs. Other embodiments of the present application also provide a scale-inhibiting alloy smelting membrane, a scale-inhibiting alloy filter material, and a method for preparing a scale-inhibiting alloy smelting membrane and a scale-inhibiting alloy filter material using the scale-inhibiting alloy smelting composition.
[0006] In a first aspect, a scale-inhibiting alloy smelting composition is provided, wherein the scale-inhibiting alloy smelting composition comprises metal materials of Fe, Zn, Sn, Ni and Cu;
[0007] Wherein, in the scale-inhibiting alloy smelting composition, the mass proportion of Fe is 12% to 29.5%, the mass proportion of Zn is 20% to 28%, the mass proportion of Sn is 13% to 16.5%, the mass proportion of Ni is 3% to 6.5%, and the balance is Cu;
[0008] Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 18.2%, 25.5%, 14.0% and 4.2% respectively, and the balance is Cu;
[0009] Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.6%, 24.0%, 15.2% and 5.0% respectively, and the balance is Cu;
[0010] Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 14.6%, 22.4%, 16.1% and 6.0% respectively, and the balance is Cu;
[0011] Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 28.0%, 25.5%, 13.6% and 3.6% respectively, and the balance is Cu;
[0012] Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.9%, 25.8%, 14.7% and 4.7% respectively, and the balance is Cu.
[0013] In a second aspect, a scale-inhibiting alloy smelting membrane is provided, wherein the scale-inhibiting alloy used in preparing the scale-inhibiting alloy smelting membrane is an alloy material containing Fe, Zn, Sn, Ni and Cu;
[0014] In the scale-inhibiting alloy, the mass proportion of Fe is 12% to 29%, the mass proportion of Zn is 20% to 25%, the mass proportion of Sn is 13% to 16%, the mass proportion of Ni is 3% to 6%, and the balance is Cu;
[0015] Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 17.85%, 24.30%, 13.69% and 3.82% respectively, and the balance is Cu;
[0016] Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.26%, 22.73%, 14.87% and 4.59% respectively, and the balance is Cu;
[0017] Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 14.23%, 21.21%, 15.76% and 5.55% respectively, and the balance is Cu;
[0018] Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 27.69%, 24.25%, 13.24% and 3.23% respectively, and the balance is Cu;
[0019] Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.61%, 24.52%, 14.37% and 4.28% respectively, and the remainder is Cu.
[0020] Optionally, the anti-scaling alloy smelting membrane has a thickness of 0.15 mm to 0.6 mm;
[0021] The crystal grains in the anti-scaling alloy are needle-shaped crystal grains. In the anti-scaling alloy smelting membrane, the angle between the length direction of each needle-shaped crystal grain and the thickness direction of the anti-scaling alloy smelting membrane is less than 20°;
[0022] Each of the needle-shaped grains has a length of 5 μm to 280 μm and a width of 1 μm to 20 μm.
[0023] In a third aspect, a method for preparing a scale-inhibiting alloy smelting membrane is provided, comprising:
[0024] Providing a scale-inhibiting alloy smelting composition as described in the first aspect;
[0025] The anti-scaling alloy smelting composition is processed by a belt-swinging smelting process to prepare the anti-scaling alloy smelting membrane.
[0026] Optionally, the scale-inhibiting alloy smelting composition is processed by a belt-swinging smelting process to prepare the scale-inhibiting alloy smelting membrane, comprising:
[0027] removing moisture from each component in the scale-inhibiting alloy smelting composition;
[0028] Under a protective atmosphere, the Fe, Sn, Ni and Cu after water removal are vacuum melted to obtain a molten metal material;
[0029] Cooling the melted metal material, adding Zn after water removal to the cooled metal material, and continuing to smelt until Zn melts, to obtain a melt material of the scale-inhibiting alloy composition;
[0030] The molten material is purified, and the purified molten material is cooled and shaped by a rotating cooling roller to obtain the anti-scaling alloy smelting membrane.
[0031] Optionally, the components in the scale-inhibiting alloy smelting composition are subjected to vacuum heating to remove moisture, wherein the vacuum degree of the vacuum heating is 100 Pa to 200 Pa, the temperature is 100° C. to 150° C., and the time is 15 min to 30 min; and / or,
[0032] The vacuum melting temperature is 1300°C to 1600°C, and the gas pressure in the cavity is 0.05 MPa to 0.07 MPa; and / or,
[0033] The temperature of the metal material after cooling is 800°C to 900°C.
[0034] Optionally, before purifying the molten material, the method further comprises: allowing the molten material to stand for 1.5 min to 3 min; and
[0035] Purifying the molten material comprises:
[0036] The molten material flows through the inclined guide plate in the belt-swinging smelting device, and the molten material is purified by the inclined guide plate.
[0037] Optionally, when the purified molten material is cooled and shaped by a rotating cooling roller, the diameter of the cooling roller is 30 cm to 50 cm, the temperature of the cooling medium in the cooling roller is 10° C. to 20° C., and the rotation speed of the cooling roller is 2 m / min to 4 m / min.
[0038] In a fourth aspect, a method for preparing a scale-inhibiting alloy filter material is provided, comprising:
[0039] The scale-inhibiting alloy filter material is prepared by cutting the scale-inhibiting alloy smelting membrane as described in the second aspect or the scale-inhibiting alloy smelting membrane prepared by the preparation method as described in the third aspect.
[0040] Optionally, the anti-scaling alloy filter material is in the form of a sheet, and the single-side area of the anti-scaling alloy filter material in the sheet is 0.2 cm 2 ~1.5cm 2 .
[0041] The above-mentioned anti-scaling alloy smelting composition, filter material, smelting membrane and preparation method thereof have the following beneficial effects:
[0042] In the anti-scaling alloy smelting composition provided in the embodiment of the present application, the nickel content is low and the iron content is relatively high, so that the cost can be reduced. By controlling the proportion of the metal raw materials in the anti-scaling alloy smelting composition within the above range, after preparing the anti-scaling alloy filter material through a suitable process such as belt smelting, the grain refinement of the anti-scaling alloy filter material can be effectively improved, so that there is no obvious segregation in the anti-scaling alloy filter material. At the same time, the anti-scaling alloy filter material can be given better corrosion resistance and scale inhibition performance, and the use of belt smelting can further improve the recovery rate, thereby further reducing the cost, solving the technical problem in the related art that the anti-scaling alloy filter material contains too much nickel, resulting in high cost of the anti-scaling alloy filter material. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 A schematic flow chart of a method for preparing a scale-inhibiting alloy smelting membrane provided in an embodiment of the present application;
[0044] Figure 2 The metallographic structure diagram of the anti-scaling alloy filter material provided in Example 1 of the present application;
[0045] Figure 3 This is the metallographic structure diagram of the anti-scaling alloy filter material provided in Comparative Example 5 of the present application. DETAILED DESCRIPTION
[0046] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0047] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "exemplarily" or "some examples" and the like are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present disclosure. The schematic representation of the above terms does not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics may be included in any one or more embodiments or examples in any appropriate manner.
[0048] Exemplary embodiments are described herein with reference to cross-sectional views and / or plan views that are idealized exemplary drawings. In the drawings, the thickness of layers and regions are exaggerated for clarity. Therefore, variations in shape relative to the drawings due to, for example, manufacturing techniques and / or tolerances are conceivable. Therefore, the exemplary embodiments should not be interpreted as being limited to the shapes of the regions shown herein, but include shape deviations due to, for example, manufacturing. For example, an etched region shown as a rectangle will typically have curved features. Therefore, the regions shown in the drawings are schematic in nature, and their shapes are not intended to illustrate the actual shape of regions of the device, and are not intended to limit the scope of the exemplary embodiments.
[0049] In this document, "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the content covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of this document. In this document, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0050] In this article, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel options of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0051] Herein, descriptions such as "optionally contain", "optionally include", etc., mean "contain or not contain". "Optional component X" means component X exists or does not exist, or means containing or not containing the component X.
[0052] In this document, the terms "first", "second", etc. in "the first aspect", "the second aspect", etc. are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0053] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0055] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0056] In this document, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc.
[0057] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0058] In this article, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0059] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0060] In view of the technical problem that the scale-inhibiting alloy filter material in the related art contains a lot of nickel, which leads to high cost of the scale-inhibiting alloy filter material, the specific implementation method of the present application is described as follows:
[0061] In a first aspect, some embodiments of the present application provide a scale-inhibiting alloy smelting composition, which comprises metal materials of Fe, Zn, Sn, Ni and Cu. In the scale-inhibiting alloy smelting composition, the mass proportion of Fe is 12% to 29.5%, the mass proportion of Zn is 20% to 28%, the mass proportion of Sn is 13% to 16.5%, the mass proportion of Ni is 3% to 6.5%, and the balance is Cu.
[0062] The anti-scaling alloy smelting composition can be used as a raw material to prepare anti-scaling alloy filter material.
[0063] For example, in the scale-inhibiting alloy smelting composition, the mass proportion of Fe can be 12%, 13%, 14%, 16%, 18%, 20%, 23%, 25%, 27% or 29.5%, in which case the mass proportion of Zn can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27% or 28%, the mass proportion of Sn can be 13%, 14%, 15% or 16.5%, the mass proportion of Ni can be 3%, 4%, 5% or 6.5%, and the sum of the mass proportions of Fe, Zn, Sn, Ni and Cu is 100%.
[0064] In the anti-scaling alloy smelting composition provided in the embodiment of the present application, the nickel content is low and the iron content is relatively high, so that the cost can be reduced. By controlling the proportion of metal materials in the anti-scaling alloy smelting composition within the above range, when the anti-scaling alloy filter material is prepared by a suitable process such as belt smelting, the grain refinement of the anti-scaling alloy filter material can be effectively improved, so that there is no obvious segregation in the anti-scaling alloy filter material. At the same time, the anti-scaling alloy filter material can be given better corrosion resistance and scale inhibition performance, and the use of belt smelting can further improve the recovery rate, thereby further reducing the cost, solving the technical problem in the related art that the anti-scaling alloy filter material contains too much nickel, resulting in high cost of the anti-scaling alloy filter material.
[0065] In some embodiments, in the anti-scaling alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 18.2%, 25.5%, 14.0% and 4.2% respectively, and the balance is Cu; or,
[0066] In the anti-scaling alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.6%, 24.0%, 15.2% and 5.0% respectively, and the balance is Cu; or,
[0067] In the anti-scaling alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 14.6%, 22.4%, 16.1% and 6.0% respectively, and the balance is Cu; or,
[0068] In the anti-scaling alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 28.0%, 25.5%, 13.6% and 3.6% respectively, and the balance is Cu; or,
[0069] In the anti-scaling alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.9%, 25.8%, 14.7% and 4.7% respectively, and the balance is Cu.
[0070] In a second aspect, some embodiments of the present application provide a scale-inhibiting alloy smelting membrane, wherein the scale-inhibiting alloy used to prepare the scale-inhibiting alloy smelting membrane is an alloy material comprising Fe, Zn, Sn, Ni and Cu. In the scale-inhibiting alloy, the mass proportion of Fe is 12% to 29%, the mass proportion of Zn is 20% to 25%, the mass proportion of Sn is 13% to 16%, the mass proportion of Ni is 3% to 6%, and the remainder is Cu.
[0071] The anti-scaling alloy smelting membrane can be obtained by smelting the anti-scaling alloy smelting composition. The anti-scaling alloy smelting composition can be prepared from a metal material containing Fe, Zn, Sn, Ni and Cu. In the anti-scaling alloy smelting composition, the mass proportion of Fe is 12% to 29.5%, the mass proportion of Zn is 20% to 28%, the mass proportion of Sn is 13% to 16.5%, the mass proportion of Ni is 3% to 6.5%, and the balance is Cu.
[0072] In the anti-scaling alloy smelting membrane provided in the embodiment of the present application, since the anti-scaling alloy used to prepare the anti-scaling alloy smelting membrane is an alloy material containing Fe, Zn, Sn, Ni and Cu, and in the anti-scaling alloy, the mass proportion of Fe is 12%~29%, the mass proportion of Zn is 20%~25%, the mass proportion of Sn is 13%~16%, the mass proportion of Ni is 3%~6%, and the balance is Cu. Therefore, the nickel content in the anti-scaling alloy is low, and the preparation of the anti-scaling alloy smelting membrane in which Fe partially replaces Ni can reduce costs, and the corrosion resistance and recovery rate of the anti-scaling alloy smelting membrane can be improved through appropriate processes, thereby further reducing costs.
[0073] In some embodiments, in the anti-scaling alloy, the mass proportions of Fe, Zn, Sn and Ni are 17.85%, 24.30%, 13.69% and 3.82% respectively, and the balance is Cu; or,
[0074] In the anti-scaling alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.26%, 22.73%, 14.87% and 4.59% respectively, and the balance is Cu; or,
[0075] In the anti-scaling alloy, the mass proportions of Fe, Zn, Sn and Ni are 14.23%, 21.21%, 15.76% and 5.55% respectively, and the balance is Cu; or,
[0076] In the anti-scaling alloy, the mass proportions of Fe, Zn, Sn and Ni are 27.69%, 24.25%, 13.24% and 3.23% respectively, and the balance is Cu; or,
[0077] In the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.61%, 24.52%, 14.37% and 4.28% respectively, and the balance is Cu.
[0078] In some embodiments, the thickness of the anti-scaling alloy smelting membrane is 0.15mm~0.6mm; the grains in the anti-scaling alloy are needle-shaped grains, and in the anti-scaling alloy smelting membrane, the angle between the length direction of each needle-shaped grain and the thickness direction of the anti-scaling alloy smelting membrane is less than 20°; the length of each needle-shaped grain is 5μm~280μm, and the width is 1μm~20μm.
[0079] Among them, the length of each needle-shaped grain is 5μm ~280μm, which means that the lengths of multiple needle-shaped grains are uneven, and the minimum can reach 5μm and the maximum can reach 280μm. In different anti-scaling alloy smelting membranes, the average length of multiple needle-shaped grains can be 120μm ~140μm. For example, in the same anti-scaling alloy smelting membrane, the average length of multiple needle-shaped grains can be any value between 120μm ~140μm. In different anti-scaling alloy smelting membranes, the average length of multiple needle-shaped grains is related to the preparation process conditions. Similarly, the width of each of the needle-shaped grains is 1μm ~20μm, which means that the width of the multiple needle-shaped grains is uneven, and the minimum can reach 1μm and the maximum can reach 20μm; similar to the length of the multiple needle-shaped grains, in the same anti-scaling alloy smelting membrane, the average width of the multiple needle-shaped grains can be any value between 2μm and 6μm. Different anti-scaling alloy smelting membranes have different average widths of the multiple needle-shaped grains depending on their different process parameters.
[0080] In these embodiments, the anti-scaling alloy smelting membrane has a suitable thickness, which can give the anti-scaling alloy a finer grain size and reduce the inclusions and segregation in the anti-scaling alloy, thereby improving the scale inhibition rate and activation current of the anti-scaling alloy filter material. At the same time, since the grains in the anti-scaling alloy are needle-shaped grains, in the anti-scaling alloy smelting membrane, multiple needle-shaped grains tend to be arranged along a direction perpendicular to the thickness of the anti-scaling alloy smelting membrane, and the angle between the length direction of each needle-shaped grain and the thickness direction of the anti-scaling alloy smelting membrane is less than 20°. Therefore, the anti-scaling alloy has a more obvious crystal orientation, thereby improving the anisotropy of the grains, and can further improve the activation current and scale inhibition performance of the anti-scaling alloy filter material.
[0081] In a third aspect, some embodiments of the present application provide a method for preparing a scale-inhibiting alloy smelting membrane, such as Figure 1 As shown, the preparation method includes steps S11) to S12):
[0082] S11), providing the scale-inhibiting alloy smelting composition as described in the first aspect.
[0083] S12), using a belt-swinging smelting process to process the scale-inhibiting alloy smelting composition to prepare a scale-inhibiting alloy smelting membrane.
[0084] In some embodiments, the scale-inhibiting alloy smelting composition is processed by a belt-swinging smelting process to prepare a scale-inhibiting alloy smelting membrane, which may include:
[0085] S121), removing moisture from each component in the scale-inhibiting alloy smelting composition;
[0086] For example, the water in each component can be removed by baking in a vacuum oven.
[0087] S122), in a protective atmosphere, vacuum melting the Fe, Sn, Ni, and Cu after removing moisture to obtain a molten metal material;
[0088] S123), cooling the melted metal material, and adding Zn after the water is removed to the cooled metal material to continue smelting until Zn is melted, so as to obtain a melt material of the scale inhibition alloy composition;
[0089] S124), purifying the molten material, and cooling and shaping the purified molten material through a rotating cooling roller to obtain a scale-inhibiting alloy smelting membrane.
[0090] In these embodiments, the moisture in Fe, Sn, Ni, Cu and Zn is removed, and the Fe, Sn, Ni and Cu after the moisture is removed are smelted to obtain a molten Fe, Sn, Ni and Cu metal mixture material, and then the melted Fe, Sn, Ni and Cu metal mixture material is cooled, and then the Zn after the moisture is removed is added to the cooled Fe, Sn, Ni and Cu metal mixture material, so as to facilitate the mutual melting of Zn with Fe, Sn, Ni and Cu at a lower temperature and reduce the gasification loss of Zn. Finally, the scale-inhibiting alloy smelting membrane is obtained by purifying the molten material and cooling and shaping the purified molten material by a rotating cooling roller. The thickness of the scale-inhibiting alloy smelting membrane can be controlled by adjusting the rotation speed of the cooling roller, so that the thickness and grain size of the scale-inhibiting alloy can be controlled, and then the scale-inhibiting alloy filter material with a higher degree of grain refinement can be obtained.
[0091] In this process, by carrying out belt smelting under a protective atmosphere, oxidation during the smelting process can be reduced, thereby reducing inclusions and segregation in the scale-inhibiting alloy, improving the recovery rate of the scale-inhibiting alloy filter material, and further reducing costs. At the same time, by testing the metallographic structure of the scale-inhibiting alloy smelting membrane, it was found that the scale-inhibiting alloy grains in the scale-inhibiting alloy smelting membrane are needle-shaped grains, and multiple needle-shaped grains tend to be arranged along a thickness direction perpendicular to the scale-inhibiting alloy smelting membrane, and the angle between the length direction of each needle-shaped grain and the thickness direction of the scale-inhibiting alloy smelting membrane is less than 20°, that is, the scale-inhibiting alloy grains in the scale-inhibiting alloy smelting membrane have obvious crystal orientation, which can improve the anisotropy of the scale-inhibiting alloy grains. The anisotropy of the grains can give the activation current of the scale-inhibiting alloy filter material a significant improvement, thereby further improving the scale inhibition rate of the scale-inhibiting alloy filter material.
[0092] In some embodiments, in S121), each component in the scale-inhibiting alloy smelting composition is subjected to vacuum heating to remove moisture, and the vacuum degree of the vacuum heating is 100 Pa to 200 Pa, the temperature is 100° C. to 150° C., and the time is 15 min to 30 min.
[0093] In some embodiments, in S122), the temperature of vacuum melting is 1300°C to 1600°C, and the gas pressure in the cavity is 0.05 Mpa to 0.07 Mpa.
[0094] In some embodiments, the temperature of the cooled metal material is 800°C to 900°C.
[0095] In some embodiments, before purifying the molten material, the method further includes: allowing the molten material to stand for 1.5 to 3 minutes; and
[0096] Purification of melt materials, including:
[0097] The molten material flows through the inclined guide plate in the belt-swinging smelting device, and the inclined guide plate is used to purify the molten material.
[0098] In these embodiments, the purification effect of the molten material can be improved, so that inclusions and segregation in the scale-inhibiting alloy can be further reduced.
[0099] In some embodiments, when the purified molten material is cooled and shaped by a rotating cooling roller, the diameter of the cooling roller is 30 cm to 50 cm, the temperature of the cooling medium in the cooling roller is 10° C. to 20° C., and the rotation speed of the cooling roller is 2 m / min to 4 m / min.
[0100] In these embodiments, the thickness and grain size of the anti-scaling alloy membrane can be controlled to obtain a highly refined anti-scaling alloy filter material, thereby improving the anti-scaling rate of the anti-scaling alloy filter material.
[0101] In a fourth aspect, some embodiments of the present application provide a method for preparing a scale-inhibiting alloy filter material, the preparation method comprising:
[0102] The scale-inhibiting alloy filter material is prepared by cutting the scale-inhibiting alloy smelting membrane as described in the second aspect or the scale-inhibiting alloy smelting membrane prepared by the preparation method as described in the third aspect.
[0103] In the preparation method of the scale-inhibiting alloy filter material provided in the embodiment of the present application, the scale-inhibiting alloy filter material of the required size and shape can be prepared by cutting the scale-inhibiting alloy smelting membrane described in the second aspect or the scale-inhibiting alloy smelting membrane prepared by the preparation method described in the third aspect, and the preparation method is simple and convenient.
[0104] In some embodiments, a cutting machine may be used to cut the anti-scaling alloy smelting membrane as described in the second aspect or the anti-scaling alloy smelting membrane prepared by the preparation method as described in the third aspect.
[0105] In some embodiments, the anti-scaling alloy filter material is in sheet form;
[0106] In these embodiments, the anti-scaling alloy filter material can be obtained by shearing the anti-scaling alloy smelting membrane, wherein the needle-shaped grains have the same characteristics as the needle-shaped grains in the anti-scaling alloy smelting membrane.
[0107] In some embodiments, the sheet-shaped anti-scaling alloy filter material can be in regular shapes such as rectangle, circle, square or any other possible irregular shapes. The single-side area of the sheet-shaped anti-scaling alloy filter material can be 0.2 cm 2 ~1.5cm 2 .
[0108] The single-side area of the sheet-shaped anti-scaling alloy filter material refers to the area of any one surface of the sheet-shaped anti-scaling alloy filter material located on one side in the thickness direction thereof.
[0109] In these embodiments, the anti-scaling alloy filter material has a higher anti-scaling rate, and also has higher corrosion resistance and recovery rate.
[0110] In order to objectively evaluate the technical effects of the embodiments of the present application, the present application will be described in detail and exemplarily through the following embodiments and comparative examples.
[0111] In the following examples and comparative examples, all raw materials can be purchased commercially, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are prepared by the same processing method.
[0112] Example 1
[0113] The preparation method of the scale-inhibiting alloy filter material provided in Example 1 is as follows:
[0114] Step (1), removing the oxide scale from the surface of the metal raw material of the scale-inhibiting alloy smelting composition, and using the metal raw material after the oxide scale removal in a ratio of 18.2% by weight of Fe, 25.5% by weight of Zn, 14.0% by weight of Sn, 4.2% by weight of Ni and the remainder of Cu to prepare a scale-inhibiting alloy filter material;
[0115] Step (2), placing Fe, Sn, Ni, Cu and Zn in the metal raw materials into a vacuum oven for drying, with the vacuum degree of the oven being 200 Pa, the heating temperature being 120° C., and the insulation time being 20 min;
[0116] Step (3), putting Fe, Sn, Ni and Cu in the anti-scaling alloy smelting composition after drying into a crucible of a vacuum melting furnace, and putting Zn into a secondary feeding hopper;
[0117] Step (4), evacuate the cavity to 2 Pa, then fill the cavity with argon protective gas until the pressure in the cavity is 0.06 MPa, and raise the temperature to 1550°C to melt all the metal materials in the crucible, and then cool it to 830°C before adding Zn;
[0118] Step (5), wait for Zn to be completely melted and stand for 2 minutes, tilt the crucible so that the molten material flows from the crucible through the inclined guide plate of the tundish and flows to the water-cooled copper roller, the diameter of the copper roller is 40 cm, the rotation speed is 3 m / min, the temperature of the cooling water in the copper roller is 15° C. The rotating copper roller allows the molten material to be quickly cooled and thrown into the collector, thereby obtaining a scale-inhibiting alloy smelting membrane;
[0119] Step (6): Use a cutting machine to cut the scale-inhibiting alloy smelting membrane into pieces with a single-side area of 1 cm 2 About flaky anti-scaling alloy filter media.
[0120] Example 2
[0121] The preparation method of the anti-scaling alloy filter material provided in Example 2 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0122] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 22.6% by mass, Zn accounts for 24.0% by mass, Sn accounts for 15.2% by mass, Ni accounts for 5.0% by mass, and the balance is Cu.
[0123] Example 3
[0124] The preparation method of the anti-scaling alloy filter material provided in Example 3 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0125] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 14.6% by mass, Zn accounts for 22.4% by mass, Sn accounts for 16.1% by mass, Ni accounts for 6.0% by mass, and the balance is Cu.
[0126] Example 4
[0127] The preparation method of the anti-scaling alloy filter material provided in Example 4 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0128] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 28.0% by mass, Zn accounts for 25.5% by mass, Sn accounts for 13.6% by mass, Ni accounts for 3.6% by mass, and the remainder is Cu.
[0129] Example 5
[0130] The preparation method of the anti-scaling alloy filter material provided in Example 5 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0131] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 22.9% by weight, Zn accounts for 25.8% by weight, Sn accounts for 14.7% by weight, Ni accounts for 4.7% by weight, and the balance is Cu.
[0132] Comparative Example 1
[0133] The preparation method of the anti-scaling alloy filter material provided in Comparative Example 1 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0134] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 32.5% by mass, Zn accounts for 26.0% by mass, Sn accounts for 14.3% by mass, Ni accounts for 4.5% by mass, and the balance is Cu.
[0135] Comparative Example 2
[0136] The preparation method of the anti-scaling alloy filter material provided in Comparative Example 2 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0137] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 11.1% by weight, Zn accounts for 25.2% by weight, Sn accounts for 15.0% by weight, Ni accounts for 4.7% by weight, and the balance is Cu.
[0138] Comparative Example 3
[0139] The preparation method of the anti-scaling alloy filter material provided in Comparative Example 3 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0140] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 23.5% by mass, Zn accounts for 25.3% by mass, Sn accounts for 18.0% by mass, Ni accounts for 4.5% by mass, and the remainder is Cu.
[0141] Comparative Example 4
[0142] The preparation method of the anti-scaling alloy filter material provided in Comparative Example 4 is substantially the same as the preparation method of the anti-scaling alloy filter material provided in Example 1, except that:
[0143] The composition of the metal raw materials in step (1) is as follows: Fe accounts for 22.4% by weight, Zn accounts for 25.8% by weight, Sn accounts for 12.1% by weight, Ni accounts for 4.6% by weight, and the remainder is Cu.
[0144] Comparative Example 5
[0145] The scale-inhibiting alloy filter material provided in Comparative Example 5 is prepared by atmospheric smelting process and turning process, and the composition of the metal raw materials in step (1) is: Fe accounts for 23.1% by mass, Zn accounts for 26.0% by mass, Sn accounts for 15.0% by mass, Ni accounts for 5.4% by mass, and the remainder is Cu.
[0146] Comparative Example 6
[0147] The scale-inhibiting alloy filter material provided in Comparative Example 6 is prepared by atmospheric smelting process and turning process, and the composition of the metal raw materials in step (1) is: Fe accounts for 5.8% by mass, Zn accounts for 26.0% by mass, Sn accounts for 15.0% by mass, Ni accounts for 15.0% by mass, and the remainder is Cu.
[0148] Test Case
[0149] 1. The metallographic structures of the anti-scaling alloy filter materials provided in Example 1 and Comparative Example 5 were observed using a metallographic microscope, and the metallographic structure diagrams were as follows: Figure 2 and Figure 3 shown.
[0150] Compare Figure 2 and Figure 3 It can be seen that the scale-inhibiting alloy filter material provided in the embodiment of the present application has a high degree of grain refinement and high anisotropy. Figure 2 It can be seen that the scale-inhibiting alloy in the scale-inhibiting alloy filter material provided in the embodiment of the present application is needle-shaped, and the arrangement direction of the multiple needle-shaped grains tends to be arranged perpendicular to the thickness direction of the scale-inhibiting alloy filter material, and the angle between the length direction of each needle-shaped grain and the thickness direction of the scale-inhibiting alloy smelting membrane is relatively small, and they basically extend along the thickness direction of the scale-inhibiting alloy smelting membrane. In addition, the main phase and grain boundary phase of the scale-inhibiting alloy in the scale-inhibiting alloy filter material provided in the embodiment of the present application are uniform and fine without obvious segregation. Figure 3 It can be seen that the scale-inhibiting alloy in the scale-inhibiting alloy filter material provided in Comparative Example 5 has relatively coarse grains and does not have obvious anisotropy.
[0151] 2. The anti-scaling alloy filter materials provided in Examples 1 to 5 and Comparative Examples 1 to 6 were loaded into filter tanks with the same mass and connected to circulating water devices respectively. The flow rates were all set to 8 L / min, the ohmmeter was adjusted to the μA gear, the positive electrode was connected to the filter tank containing the anti-scaling alloy filter material, the distance between the negative electrode and the positive electrode was 20 cm, and the value of the ohmmeter 10 minutes after the circulating water was turned on was the size of the activation current. The specific test results are shown in Table 1 below.
[0152] 3. The scale-inhibiting alloy filter materials provided in Examples 1 to 5 and Comparative Examples 1 to 6 were dried under the same conditions, and after cooling, the same weight was weighed and loaded into filter tanks, respectively connected to 5wt% sodium chloride circulating water devices, and the flow rate of 5wt% sodium chloride circulating water was set to 8L / min. When the water flow rate was 200m³, the scale-inhibiting alloy filter materials provided in each embodiment and comparative example were taken out, washed with pure water, dried, cooled, and weighed after testing. The weight loss rate of the scale-inhibiting alloy filter materials provided in each embodiment and comparative example was calculated as an indicator for judging corrosion resistance. The specific test results are shown in Table 1 below.
[0153] 4. The scale-inhibiting alloy filter materials provided in Examples 1 to 5 and Comparative Examples 1 to 6 were prepared into filter elements of the same specifications. Pure water, anhydrous calcium chloride and sodium bicarbonate were used to prepare test water with a total hardness of 350 mg / L and a total alkalinity of 160 mg / L. The test water was passed through the filter element with the scale-inhibiting alloy filter material at a rate of 6 L / min. A water sample was obtained after 10 minutes, and the scale-inhibiting performance of the scale-inhibiting alloy filter materials provided in each embodiment and comparative example was tested in accordance with GB / T 16631 to 2019. The test results are shown in Table 1 below.
[0154] 5. Weigh the weight m1 of the anti-scaling alloy filter material provided by Examples 1 to 5 and Comparative Examples 1 to 6, and divide the weight m1 by the weight m2 of the raw materials input in the corresponding Examples and Comparative Examples to calculate the recovery rate of the anti-scaling alloy filter material of each Example and Comparative Example. The calculation results are shown in Table 1 below.
[0155] Table 1
[0156]
[0157] It can be seen from Table 1 that under the same atmosphere protection belt smelting conditions, the recovery rate of the scale-inhibiting alloy filter material provided by Examples 1 to 5 is significantly higher, and the high level of iron will not cause a large corrosion loss rate of the scale-inhibiting alloy filter material. Under the strengthening effect of the anisotropy of the oriented crystallized grains, the activation current and scale inhibition rate of the scale-inhibiting alloy filter material are significantly improved.
[0158] By comparing Examples 1 to 5 with Comparative Examples 1 to 6, the recovery rate of the anti-scaling alloy filter material prepared by the atmosphere-protected belt-spinning smelting process is significantly higher.
[0159] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that when the Fe content is too high, the corrosion resistance is poor.
[0160] By comparing Examples 1 to 5 with Comparative Example 2, it can be seen that when the Fe content is too low, the activation current is small and the scale inhibition rate becomes low.
[0161] By comparing Examples 1 to 5 with Comparative Example 3, it can be seen that when the Sn content is too high, the material is brittle and breaks during cutting, resulting in a low recovery rate.
[0162] By comparing Examples 1 to 5 with Comparative Example 4, it can be seen that when the Sn content is too low, the activation current is small and the scale inhibition rate becomes low.
[0163] By comparing Example 5 and Comparative Example 5, it can be seen that when atmospheric smelting is adopted, the recovery rate, activation current and scale inhibition rate are all lowered, and the corrosion resistance is deteriorated.
[0164] Comparison of Comparative Example 6 with Comparative Example 5 shows that when the alloy with high Ni content is smelted in the atmosphere, although the corrosion loss rate is less than 15%, the recovery rate is low.
[0165] In summary, the embodiments of the present application can prepare scale-resistant alloy filter materials with a large tendency of oriented crystallization and large grain anisotropy. The activation current increases with the increase of the anisotropy of the material, and the atmosphere-protected belt-spinning smelting process is used to reduce the inclusions, segregation and oxidation in the scale-resistant alloy filter materials, so that the scale-resistant alloy filter materials can be directly cut from the scale-resistant alloy smelting membrane, with high recovery rate and low cost. In addition, the scale-resistant alloy filter materials provided in the embodiments of the present application have a high degree of grain refinement, which can improve the activation current and scale inhibition rate of the scale-resistant alloy filter materials. By using iron instead of nickel, the grains can be refined through belt-spinning smelting, which can reduce the cost of raw materials without sacrificing corrosion resistance.
[0166] It can be seen that the scale-inhibiting alloy filter material provided in the embodiments of the present application has the advantages of low cost, strong corrosion resistance, and high comprehensive performance levels such as scale inhibition rate and activation current.
[0167] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0168] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A scale-inhibiting alloy smelting composition, characterized in that: The scale-inhibiting alloy smelting composition comprises metal materials of Fe, Zn, Sn, Ni and Cu; Wherein, in the scale-inhibiting alloy smelting composition, the mass proportion of Fe is 12% to 29.5%, the mass proportion of Zn is 20% to 28%, the mass proportion of Sn is 13% to 16.5%, the mass proportion of Ni is 3% to 6.5%, and the balance is Cu; Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 18.2%, 25.5%, 14.0% and 4.2% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.6%, 24.0%, 15.2% and 5.0% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 14.6%, 22.4%, 16.1% and 6.0% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 28.0%, 25.5%, 13.6% and 3.6% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy smelting composition, the mass proportions of Fe, Zn, Sn and Ni are 22.9%, 25.8%, 14.7% and 4.7% respectively, and the balance is Cu.
2. A scale-inhibiting alloy smelting membrane, characterized in that: The scale-inhibiting alloy used in the scale-inhibiting alloy smelting membrane is an alloy material containing Fe, Zn, Sn, Ni and Cu; In the scale-inhibiting alloy, the mass proportion of Fe is 12% to 29%, the mass proportion of Zn is 20% to 25%, the mass proportion of Sn is 13% to 16%, the mass proportion of Ni is 3% to 6%, and the balance is Cu; Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 17.85%, 24.30%, 13.69% and 3.82% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.26%, 22.73%, 14.87% and 4.59% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 14.23%, 21.21%, 15.76% and 5.55% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 27.69%, 24.25%, 13.24% and 3.23% respectively, and the balance is Cu; Optionally, in the scale-inhibiting alloy, the mass proportions of Fe, Zn, Sn and Ni are 22.61%, 24.52%, 14.37% and 4.28% respectively, and the remainder is Cu.
3. The scale-inhibiting alloy smelting membrane according to claim 2, characterized in that: The thickness of the anti-scaling alloy smelting membrane is 0.15mm~0.6mm; The crystal grains in the anti-scaling alloy are needle-shaped crystal grains. In the anti-scaling alloy smelting membrane, the angle between the length direction of each needle-shaped crystal grain and the thickness direction of the anti-scaling alloy smelting membrane is less than 20°; Each of the needle-shaped grains has a length of 5 μm to 280 μm and a width of 1 μm to 20 μm.
4. A method for preparing a scale-inhibiting alloy smelting membrane, characterized in that: include: Providing a scale-inhibiting alloy smelting composition as claimed in claim 1; The anti-scaling alloy smelting composition is processed by a belt-swinging smelting process to prepare the anti-scaling alloy smelting membrane.
5. The preparation method according to claim 4, characterized in that: The scale-inhibiting alloy smelting composition is processed by a belt-swinging smelting process to prepare the scale-inhibiting alloy smelting membrane, comprising: removing moisture from each component in the scale-inhibiting alloy smelting composition; Under a protective atmosphere, the Fe, Sn, Ni and Cu after water removal are vacuum melted to obtain a molten metal material; Cooling the melted metal material, adding Zn after water removal to the cooled metal material, and continuing to smelt until Zn melts, to obtain a melt material of the scale-inhibiting alloy composition; The molten material is purified, and the purified molten material is cooled and shaped by a rotating cooling roller to obtain the anti-scaling alloy smelting membrane.
6. The preparation method according to claim 5, characterized in that: The components in the anti-scaling alloy smelting composition are subjected to vacuum heating to remove moisture, wherein the vacuum degree of the vacuum heating is 100 Pa to 200 Pa, the temperature is 100° C. to 150° C., and the time is 15 min to 30 min; and / or, The vacuum melting temperature is 1300°C to 1600°C, and the gas pressure in the cavity is 0.05 MPa to 0.07 MPa; and / or, The temperature of the metal material after cooling is 800°C to 900°C.
7. The preparation method according to claim 5, characterized in that: Before purifying the molten material, the method further includes: allowing the molten material to stand for 1.5 min to 3 min; and Purifying the molten material comprises: The molten material flows through the inclined guide plate in the belt-swinging smelting device, and the molten material is purified by the inclined guide plate.
8. The preparation method according to claim 5, characterized in that: When the purified molten material is cooled and shaped by a rotating cooling roller, the diameter of the cooling roller is 30 cm to 50 cm, the temperature of the cooling medium in the cooling roller is 10° C. to 20° C., and the rotation speed of the cooling roller is 2 m / min to 4 m / min.
9. A method for preparing a scale-inhibiting alloy filter material, characterized in that: include: The scale-inhibiting alloy filter material is prepared by cutting the scale-inhibiting alloy smelting membrane according to any one of claims 2 to 3 or the scale-inhibiting alloy smelting membrane prepared by the preparation method according to any one of claims 4 to 8.
10. The preparation method according to claim 9, characterized in that: The anti-scaling alloy filter material is in the form of a sheet, and the single-side area of the anti-scaling alloy filter material in the sheet is 0.2 cm 2 ~1.5cm 2 .
Citation Information
Patent Citations
Full-intelligent scale-preventing and scale-removing alloy and preparation method thereof
CN107338368A
Scale inhibition alloy, preparation method thereof and scale inhibition sheet made of scale inhibition alloy
CN117721344A